2017
DOI: 10.1016/j.neuropsychologia.2017.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Temporal gradient during famous face naming is associated with lower cerebral blood flow and gray matter volume in aging

Abstract: Objective Evidence suggests that famous face naming may be a cognitive ability especially sensitive to the early pathological processes of Alzheimer’s disease (AD) and that those at risk for AD may demonstrate a Ribot temporal gradient (RTG), characterized by better performance for naming remote famous faces than for naming recent famous faces. Reductions in cerebral blood flow (CBF) and gray matter volume (GMV) have been implicated in the neuropathological cascade of AD and show utility as biomarkers of AD ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 47 publications
2
9
0
2
Order By: Relevance
“…Cattell BOLD activity Age-related decreases in baseline cerebral blood flow (CBF), assessed with a non-invasive MR-perfusion technique, related to behaviourally relevant BOLD activity evoked by demanding problem-solving. Our findings are consistent with previous studies relating baseline CBF to performance on tasks carried outside the scanner (Bangen et al, 2014;Hays et al, 2017). We extend these lines of work by showing that baseline CBF is linked to BOLD activity, with behavioural correlation across individuals.…”
Section: Age Differences In Baseline Cerebral Blood Flow Are Related To Behaviour-relevantsupporting
confidence: 92%
See 1 more Smart Citation
“…Cattell BOLD activity Age-related decreases in baseline cerebral blood flow (CBF), assessed with a non-invasive MR-perfusion technique, related to behaviourally relevant BOLD activity evoked by demanding problem-solving. Our findings are consistent with previous studies relating baseline CBF to performance on tasks carried outside the scanner (Bangen et al, 2014;Hays et al, 2017). We extend these lines of work by showing that baseline CBF is linked to BOLD activity, with behavioural correlation across individuals.…”
Section: Age Differences In Baseline Cerebral Blood Flow Are Related To Behaviour-relevantsupporting
confidence: 92%
“…Cerebral blood flow (CBF) changes early in experimental models of dementia, leading to neuronal dysfunction, and loss independently of amyloid-b-dependent contributions (Iadecola, 2004;Zlokovic, 2011;Kisler et al, 2017;Sweeney et al, 2018Sweeney et al, , 2019. In healthy ageing, previous reports have linked the effects of age on baseline CBF to behavioural performance measured outside of the scanner (Bangen et al, 2014;Hays et al, 2017;Leeuwis et al, 2018). However, brain perfusion measurements are highly dependent on other physiological factors such as autoregulation modulators (Lemkuil et al, 2013), medication, time of day, levels of wakefulness (Patricia et al, 2014), physical exercise, caffeine or smoking before the scan (Domino et al, 2004;Addicott et al, 2009;Merola et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite increasing studies of ASL on dementia, only a few on individuals with SCD are available, and the findings seem to be not in agreement. Hays et al (2018) have demonstrated significant negative correlations between verbal memory and CBF within the posterior cingulate cortex, middle temporal 10.3389/fnins.2022.961164 gyrus, hippocampus, fusiform gyrus, and inferior frontal gyrus in patients with SCD. Another observational study has revealed that compared with elderly controls, participants with SCD presented a significant decline in CBF values, mainly in the hippocampal and posterior cingulate cortex (Yang et al, 2021).…”
Section: Introductionmentioning
confidence: 97%
“…Long et al found moderate atrophy in the thalamus, accumbens, pallidum, and putamen; the hippocampal volume slightly increased at 40 years and decreased after the age of 50 years. The hippocampus plays an important role in the human brain due to its structural and functional relevance to cognition and memory‐related diseases . However, currently, few studies have reported the changes in the hippocampal subfields with aging.…”
mentioning
confidence: 99%
“…The hippocampus plays an important role in the human brain due to its structural and functional relevance to cognition and memory-related diseases. 17,18 However, currently, few studies have reported the changes in the hippocampal subfields with aging. A clear understanding of the relationship between the volume of deep nuclei and age is necessary to identify the difference between normal aging and psychotic and neuropathic disorders related to age.…”
mentioning
confidence: 99%